2020
DOI: 10.1302/2058-5241.5.190070
|View full text |Cite
|
Sign up to set email alerts
|

Advanced techniques in amputation surgery and prosthetic technology in the lower extremity

Abstract: Bone-anchored implants give patients with unmanageable stump problems hope for drastic improvements in function and quality of life and are therefore increasingly considered a viable solution for lower-limb amputees and their orthopaedic surgeons, despite high infection rates. Regarding diversity and increasing numbers of implants worldwide, efforts are to be supported to arrange an international bone-anchored implant register to transparently overview pros and cons. Due to few, but high-quality, articles abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…Given that modern prosthesis techniques are quite advanced, if our patient had chosen AK amputation followed by bionic reconstruction combined with the beneficial effects of targeted muscle innervation and regenerative peripheral nerve interface [14] , a similar functional effect to rotationplasty might have been achieved. However, not every patient has the same access to cutting-edge technology or the ability to afford it.…”
Section: Discussionmentioning
confidence: 99%
“…Given that modern prosthesis techniques are quite advanced, if our patient had chosen AK amputation followed by bionic reconstruction combined with the beneficial effects of targeted muscle innervation and regenerative peripheral nerve interface [14] , a similar functional effect to rotationplasty might have been achieved. However, not every patient has the same access to cutting-edge technology or the ability to afford it.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies among adults with transfemoral amputations have shown improved prosthetic satisfaction, sitting comfort, mobility and reduced cost of energy while walking with BAP. 9,10 Several different implant systems are available globally; however, the OPRA TM Implant System (Integrum, Sweden) is currently the only system FDA approved for use in adults at the transfemoral level and available with humanitarian exemption for transhumeral amputees (Figure 2). Other designs have been used in the U.S. on a custom or experimental basis.…”
Section: Bone Anchored Prostheses (Bap)mentioning
confidence: 99%
“…11 While most studies across the various available implants demonstrate improved quality of life with BAP, there remains a high infection rate. 10,[12][13][14] The feasibility of BAPs in growing children is unknown due to the risk of osseous overgrowth and implant infection. However, osseointegration can similarly be used to improve prosthesis use and function in skeletally mature adolescents with limb differences; this population should be considered for future clinical trials with BAP.…”
Section: Bone Anchored Prostheses (Bap)mentioning
confidence: 99%
“…The methods, techniques and results of transtibial amputations are well described in the available literature, [1][2][3][4][5][6][7][8][9] as well as the effect of local, due to neuroma, and phantom pain syndrome on the quality of life of patients. 8,9 Emphasis is placed on the excessive mobility of the residual fibula, its valgus deviation, pain syndrome on the outer surface of the residual limb, and difficulties or impossibility of prosthesis.…”
Section: Introductionmentioning
confidence: 99%